Mucosal associated Lymphoid Tissue Lymphoma of the uvea: an analysis of 3 cases - Zhenyu Wang; Yueming Liu; Jing Mo; Xusheng Cao; Xiaolin Xu; Lin Shen; Hong Wang; Wenbin Wei (BMC Ophthalmology, 2022)
Abstract Background Ocular mucosa-associated lymphoid tissue (MALT) lymphoma involving orbit and conjunctiva usually has an indolent clinical course with “salmon patch” mass as typical presentation. This study is to report a series of rare cases and investigate the clinical and pathological features of ocular MALT lymphoma that involved uveal tissue primarily and presented as posterior scleritis. Methods This retrospective, observational study was conducted at Beijing Tongren Hospital. From 2018 to 2020, 3 cases of 3 eyes (2 female patients and 1 male patient) with ocular MALT lymphoma that involved uveal tissue primarily and presented as posterior scleritis were included in the study. All patients had complaints of red eyes with blurred vision. The average age was 56.33 ± 2.08 years old and the average time from initial diagnosis to pathological diagnosis was 3.00 ± 1.73 months. Ophthalmic examinations including best-corrected visual acuity (BCVA), intraocular pressure (IOP), slit lamp microscope examinations, fundus photography, B-scan ultrasonography, ultrasound biomicroscope (UBM), optical coherence tomography (OCT), fundus fluorescein angiography (FFA) and indocyanine green angiography (ICGA) were conducted. Systemic workups including orbital magnetic resonance imaging (MRI), positron emission tomography-computed tomography (PET-CT) and blood autoimmune antibody tests were also conducted. Pathological tissue from patients were obtained through surgeries. Biopsy examinations were performed to accurately determine pathological diagnosis. All the information of clinical, imaging and pathological changes were collected and analyzed. Results At the initial diagnosis, the BCVA of involved eyes decreased seriously while the IOP were normal. All involved eyeball showed extensive hyperemia and local thickening in the wall of eyeballs. B-scan ultrasonography showed mass with abundant blood and irregular cysts inside the eyeball wall and in the retrobulbar orbit, surrounding the ocular wall and optic nerve. UBM showed solid lesions with low and medium echo under the conjunctiva and inside the ciliary body of 2 cases. OCT showed posterior polar wavy rise of RPE and local neuroepithelial detachment in all cases. FFA and ICGA showed vascular abnormalities (patch-like strong fluorescence and fluorescence leakage) and local thickening in retina and choroid (Rectangle-like weak fluorescence below the macula). The posterior wall of the eyeball was thickened and enhanced in MRI. PET-CT also showed thickening of posterior wall of eyeballs and increased metabolic activity but there was no sign of autoimmune disease. All patients were diagnosed as MALT lymphoma through pathologic examinations of biopsy tissue. Conclusions The onset of primary ocular MALT lymphoma in uvea is hidden. The early clinical manifestations are lack of specificity and misleading. B-scan ultrasonography has characteristic manifestations and is valuable in diagnosis. However, pathological diagnosis through tissue biopsy is irreplaceable.